Definição de reserva de espaço durante o PDP para assegurar manutenção de componentes-chave - Marcon Junior, Simão (2015)
Even though maintainability is regarded as important in the PDP, both literature and PDP methodologies deal with this parameter superficially and in an indirect manner. With that, it becomes clear that the proper addressing of the maintainability parameter is necessary in the early stages of the PDP when the costs associated with design changes are smaller. One way of addressing maintainability is through the use of space claims. The space claims have as their goal to assure the virtual analysis using CAD systems, during product development, of the space that will be used by technicians to perform product maintenance. Currently, the space claims are done manually, spending valuable development time/hours and dependent on the previous knowledge of experts. The purpose of this thesis is to propose a set of procedures and a computer application to assist the product development team in the treatment of maintainability parameter, through the usage of space claims, agile and concisely. The methodology used to reach the objectives is supported by three main components: i/understanding the relevant literature; ii/ developing the needed procedures and a computer application to assist the product development team, during PDP, to address maintainability; and iii/results validation. With this knowledge, it was possible to design the procedures and a computer application aiming to address the maintainability, through the space claims, during PDP. The proposal was validated through the presentation of procedures and computer application to a professional group in the automotive industry. By collecting answers originated from two questionnaires, could evaluate the results. The results show that set of procedures and computer application have a potential to improve the way of address maintainability during PDP.